ANALISIS ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN COVID-19 DI INDONESIA - Zeze Zakaria Hamzah; Benny Osta Nababan; Heru Satria Rukmana; Monica Dyanti Sitinjak (Institut Teknologi dan Bisnis Dewantara, 2023)
This study aims to determine and analyze whether there is a difference in the average abnormal return before and after the announcement of the Covid-19 virus was first confirmed in Indonesia, to find out and analyze whether there is a difference in the average security return variability before and after the announcement of the Covid-19 virus. First confirmed in Indonesia and to find out and analyze whether there is a difference in the average trading volume activity before and after the announcement of the first confirmed Covid-19 virus in Indonesia. The type of research used in this research is quantitative research. The sample used for this study was four non-Islamic state-owned banks. The results of this study indicate that there is no difference in abnormal returns between before and after the event of the First Confirmed Covid-19 Announcement in Indonesia, there is a difference in Security Return Variability (SRV) between before and after the occasion of the First Confirmed Covid-19 Announcement in Indonesia, and there is no the difference in Trade Volume Activity (TVA) between before and after the First Confirmed Covid-19 Announcement event in Indonesia.